Non-contact and liquid–liquid interfacing triboelectric nanogenerator for self-powered water/liquid level sensing. (June 2020) - Wang, Peng; Zhang, Steven; Zhang, Lei; Wang, Longfei; Xue, Hao; Wang, Zhong Lin
Abstract: Triboelectric nanogenerators (TENG) based on liquid-solid or solid-solid contact have attracted much attention in sensing applications recently. However, the stain caused from external environment and high friction over triboelectric interface are two important issues yet to be solved. To address these issues, a novel magnetic field assisted non-contact TENG is designed by driving the motion of ferrofluid in a sealed tube under an external magnetic field without direct contact. The as-designed TENG can separate the external mechanical motion from the inner triboelectric process, thereby solving the potential stain problem over the triboelectric interface from external environment. Furthermore, a lubricant oil layer is introduced between ferrofluid and substrate to construct a liquid–liquid triboelectric interface, which facilitates the sliding behavior of ferrofluid. This design helps to extend the range of linear relationship between triboelectric current peak value and the ferrofluid motion velocity over its surface, thereby breaking the motion velocity measurement limit of TENG as a velocity sensor. Finally, its potential application is demonstrated as a self-powered water/liquid level sensor. This work provides a novel type of non-contact TENG, and shows triboelectrification on liquid–liquid contact. The novel TENG could be further applied as a highly sensitive sensor in harsh environment. Graphical abstract: The application of triboelectric nanogenerators (TENG) is challenged by the stain and high friction issues over triboelectric interface. The authors propose a novel non-contact and liquid-liquid interfacing TENG, which addresses these issues by separating the external mechanical motion with the inner triboelectric process, and construction a liquid/liquid triboelectric interface to reduce sliding friction. Image 1 Highlights: A novel non-contact TENG was designed to address stain issue over contact interface. A liquid–liquid triboelectric interface was constructed to reduce interface friction. Its working principle was proposed based on simulations and experiment verification. Its advanced performance as a self-powered water level sensor was demonstrated.